Odpowiedzi

2010-03-14T20:39:58+01:00
B. 1-6/7x = 4/7 /*7x
1-6= 4x
-5= 4x /:4
x = -5/4
x= -1 1/4

d. x/6-1/6 = 1 /*6
x-1=6
x=6+1
x=7

f. 2/5(3-x) = -2 /*5

2(3-x) = -10
6-2x = -10
-2x = - 10-6
-2x= -16 /:(-2)
x=8

h. 1/5(x-3)=9-x /*5
x-3 = 45-5x
x+5x = 45+ 3
6x=48 /:6
x=8
5 2 5
Najlepsza Odpowiedź!
2010-03-14T20:42:50+01:00
B. 1-6/7x = 4/7 / *7
7-6x = 4
-6x = 4-7
-6x = -3 / :(-6)
x = ³/₆
x = ½

d. x/6 - 1/6 = 1 / *6
x - 1 = 6
x = 6+1
x = 7

f. 2/5 (3-x) = -2
⁶/₅ - ²/₅ x = -2
- ²/₅ x = -2 - 1 ⅕
- ²/₅ x = -3 ⅕ / * (- ⁵/₂)
x = - ¹⁶/₅ * (- ⁵/₂)
x = 8

h . 1/5 (x-3) = 9-x
⅕ x - ³/₅ = 9- x
⅕ x+x = 9 + ³/₅
1 ⅕ x = 9 ³/₅
⁶/₅ x = ⁴⁸/₅ / * ⁵/₆
x = ⁴⁸/₅* ⁵/₆
x = 8
12 4 12
b) odpowiedź ma być x= -2,5